REISOLATION AND REIDENTIFICATION OF ANTIBIOTIC RESISTANT BACTERIA FROM THE TOILET DOOR HANDLES IN INTI INTERNATIONAL UNIVERSITY - Waisimon, Margret (2018)
Studies have shown that bacterial contamination are common on inanimate surfaces. One of the common surfaces that can transmit bacteria is toilet door handles. Improper hygiene practice of toilet users can be the cause of transmission of pathogens including antibiotic resistant bacteria. Antibiotic resistant bacteria were isolated form the toilet door handles in INTI International University from a previous study. However, these isolates were poorly identified, and the complete antibiogram pattern were not done as well as the pure cultures were not preserved. Thus, the aim of this study was to reisolate and reidentify the antibiotic resistant bacteria from the toilet door handles in INTI International University as well as to determine the resistant pattern of the isolates using the antibiotic disk diffusion method. Bacterial sample were obtained from each toilet cubicles in the female toilets in the academic block of INTI International University. The sample were inoculated in nutrient broth and incubated at 200rpm, 37℃ for 16-18hr. The pure culture of 46 isolates were identified using several confirmatory tests such as gram staining, catalase test, oxidase test, TSI agar test and IMVIC test. Furthermore, the isolates were grown also grown onto MSA and MacConkey agar to further identify the genus and species. Out of 46 pure isolates, 42 isolates were able to be identified its genus and species using Bergey’s Manual of Determinative Bacteriology 9th edition, whereas, 4 isolates cannot be identified. Several possible genus and species were identified such as Staphylococcus aureus, Staphylococcus epidermidis, Bacillus spp and Salmonella spp. Different antibiotics such as amoxicillin, ampicillin, cefoxitin, penicillin G, ofloxacin, vancomycin as well as gentamycin were used to determine the antibiotic susceptibility pattern of gram positive and gram negative isolates based on the Clinical and Laboratory Standards Institute (CLSI) 27th Edition. From a total of 42 identified isolates, 10 isolates were resistant to antibiotics. Out of 11 isolates of Staphylococcus aureus, 1 isolate (2.38%) was resistance to cefoxitin explaining the presence of methicillin-resistant Staphylococcus aureus (MRSA) isolated from the toilet door handles. Meanwhile, 5 isolates of S. epidermidis (11.90%) were resistant toward both penicillin G and cefoxitin showing the presence of multidrug resistant (MDR) bacteria. This study shows that the toilet door handles can be one of the significant inanimate surface to transmit antibiotic resistant bacteria from one individual to another in INTI International University. Personal hygiene is important to remove the spread of these pathogen in the environment.